An interdisciplinary method for assessing IPM potential: case study in Scottish spring barley - Stacia Stetkiewicz; Ann Bruce; Fiona J. Burnett; Richard A. Ennos; Cairistiona F. E. Topp (CABI Agriculture and Bioscience)
Abstract A method is proposed which considers Integrated Pest Management (IPM) through several lenses, in order to obtain a more holistic view of the potential for IPM, and is described using a case study of Scottish spring barley. Long-term experimental field trial databases are used to determine which management methods are best suited to the system at hand. Stakeholder engagement provides insight into which of these methods are most likely to be taken up by farmers. Finally, a database of commercial practice allows an estimate of the potential for improving management patterns, based on current levels of IPM uptake across a wider sample of Scottish farmers. Together, these diverse sources of information give a more complete view of a complex system than any individual source could and allow the identification of IPM methods which are robust, practical, and not already in widespread use in this system. Bringing together these sources of information may be of particular value for policy and other decision makers, who need information about strategies which are both practical and likely to have a large positive impact. In the case of Scottish spring barley, there is good potential to reduce the need for fungicide use through the increased use of highly resistant barley varieties.